Development and validation of a prognostic nomogram for extrahepatic bile duct adenocarcinoma - Zhang, Shiyao; Cui, You; Zhao, Xinyu; Zhang, Qi; Li, Chunqiang; Huang, Qianpeng; Liu, Gang (Frontiers in Oncology, 2022)
Objective The aim of this study is to establish a prognostic nomogram for patients with extrahepatic bile duct adenocarcinoma (EBDA). Methods From the Surveillance, Epidemiology, and End Results database, we retrieved clinical data from 1,485 patients diagnosed with EBDA between 2004 and 2015. These patients were randomly assigned to either the training or validation group in a ratio of 2:1. Cox proportional risk regression models were used to analyze the association of each variable with overall survival (OS). Univariate and multifactorial Cox regression analyses were performed to identify prognostic factors, and prognostic nomograms were created on the basis of the results of Cox multifactorial regression analysis. Performance was assessed by calibration curves and ROC curves. Internal validation was performed using the validation cohort. The Kaplan–Meier method was used to perform log-rank constructions for different risk groups. Results The results indicated that age, race, N and M stages of tumor–lymph node metastases based on AJCC version 6, surgery, and chemotherapy were independent prognostic factors for OS in patients with EBDA. The constructed nomograms showed decent classification in predicting both 3- and 5-year survival rates. The calibration curves also show a high degree of agreement between the predicted and actual operating systems. Conclusions The nomogram that we constructed provides a relatively accurate and applicable prediction of survival outcome in patients with EBDA, which helps to provide reference and guidance for patient treatment.